Bitter Truth of Child Labour in India - Mohan, Mayank (Journal of Commerce and Trade, 2018)
Child labour is a complex problem that is basically rooted in poverty. The government is quite committed to the cause of controlling and eliminating child labour from India. India has all along followed a proactive policy with respect to the problem of child labour, and has stood for the constitutional, statutory and developmental measures to combat child labour. Child labour laws and legislations have been enacted in our country, but the condition of child labourers still remains the same. This is because of lack of effective machinery for the implementation of such laws as well as the lack of awareness among labourers and employers about the restrictions on the employment of children as workers.